Regular versus lump-sum payments in union contracts and household consumption - Effrosyni Adamopoulou; Roberta Zizza (European Central Bank (ECB), 2017)
We use information on monthly wage increases set by collective agreements in Italy and exploit their variation across sectors and over time in order to examine how household consumption responds to different types of positive income shocks (regular tranches versus lump-sum payments). Focusing on single-earner households, we find evidence of consumption smoothing in accordance with the Permanent-Income Hypothesis, since total and food consumption do not exhibit excess sensitivity to anticipated regular payments. Consumption does not respond at the date of the announcement of income increases either, as these are known to compensate workers for the overall loss in their wages' purchasing power. However, consumption responds, albeit a little, to transitory and less anticipated one-off payments, as the expenditures on clothing & shoes increase upon the receipt of the lump-sum payments. This behaviour is consistent with bounded rationality as consumers do not consider the lump-sum as part of the overall wage inflation adjustment.
Keywords: D12; E21; J51; 330; bounded rationality; consumption; permanent income hypothesis; union contracts